Ethical dimensions of agroecology criticism to the agrobiotechnology - Altieri, Miguel A. (Acta Bioethica, 2003)
The goal of this report is to put into question the false promises that agroindustry has made about genetic engineering in agriculture. They have promised that the transgenic crops should generate agriculture less dependent of chemical supplies, it should increase the productivity and it would help to reduce the environmental problems. On the other hand, this paper analyzes the environmentalist criticism to the biotechnology, specially the deep worry about the social, economic moral, religious, and cultural effects or values that have been ignored in the biotechnological development of the agrobiotechnology. The author concludes starting that it has arrived the social moment to challenge the reality of genetic engineering. The biotechnology companies must feel the impact of environmentalist, labor and rural movements, so that they may reorient their work for the benefit of society and nature.